Measures to Control Invasive Crayfish Species in Switzerland: A Success Story? - Krieg, Raphael; King, Alex; Zenker, Armin (Frontiers in Environmental Science, 2020)
Invasive crayfish species were first documented in Switzerland in the 1970s. Today, American crayfish species dominate in most major lakes and streams in Switzerland. In combination with the crayfish plague, they pose a substantial threat to our native crayfish. In the past twenty years, various techniques were applied to reduce negative impacts of invasive crayfish in Switzerland: intensive trapping, introduction of predatory fish, construction of crayfish barriers and destruction or temporary draining of waters. Trapping and introduction of predatory fish led to a reduction in population density but never led to the extinction of a population. Filling and temporary drainage of isolated ponds, in combination with calcium hydroxide application was successful in eradicating populations of invasive crayfish. Invasive crayfish have not yet reached crayfish barriers, therefore, long-term functionality of these barriers still needs to be proven. However, functional controls with native crayfish have shown that barriers prevent their upstream movement. Implementation of crayfish barriers is the most promising method to protect native crayfish from displacement by invasive crayfish species. Many measures are expensive, time consuming and show little or no success in controlling invasive crayfish. Therefore, we recommend to focus on implementing drastic measures, such as filling-in or draining of isolated waters or an combination of various methods for population reduction.